Kinetics of endothelialization of the multilayer flow modulator and single-layer arterial stents. (February 2016) - Sultan, Sherif; Kavanagh, Edel P; Bonneau, Michel; Kang, Chantal; Alves, Antoine; Hynes, Niamh M
The multilayer flow modulator (MFM; Cardiatis, Isnes, Belgium) is a self-expandable mesh of braided cobalt alloy wires, used for treatment of aortic and peripheral aneurysms. To further improve our understanding of this novel technology, the endothelialization kinetics of the MFM was investigated and compared with those of two marketed single-layer stents. Five porcine animal models were used in which a total of 19 stents were implanted in the iliac and carotid arteries between one and five weeks before sacrifice. All 19 stents were successfully delivered. For all devices, nonsignificant signs of inflammation or thrombosis were noted, and there was no evidence of local intolerance. The MFM developed a thin layer of endothelial cells earlier and was associated with less neointimal development than the two single-layer stents. A differing phenomenon of integration was also revealed and hypothesized as endothelialization from adhesion of circulating endothelial progenitor cells, as well as adhesion from the arterial wall, and also by the differences in trauma exposed to the arterial wall.